Front Cover: Enhancing Robustness of Sortase A by Loop Engineering and Backbone Cyclization (Chem. Eur. J. 60/2020). Issue 60 (16th September 2020) - Zou, Zhi; Mate, Diana M.; Nöth, Maximilian; Jakob, Felix; Schwaneberg, Ulrich
Abstract : Sortase‐mediated ligation (sortagging) has emerged as one of the most popular methodologies for site‐specific modification of proteins. The cover image shows a loop engineering and subsequent head‐to‐tail backbone cyclization of Staphylococcus aureus sortase A (SaSrtA, the engineered loop and fused termini are highlighted in cyan). The reengineered SaSrtA has an enhanced robustness towards thermal and chemical denaturation. More information can be found in the Communication by U. Schwaneberg et al. on page 13568 .